(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2023)
Obstacle detection can be considered central and paramount in designing mobile robots. This technique enables mobile robots equipped with sensors to transverse and maneuver freely in an environment preventing damage as a result of a collision with obstacles in its path. Several systems with different approaches have been developed for the anti-collision of a robot with obstacles. The approach to Sensor selection, path planning, and navigation processes determines the operation of such a system and differs from one another. This paper presents a low-cost ultrasonic distance sensor for obstacle detection to enhance anti-collision in mobile robot navigation. The system is designed with the C/C++ programming of the Arduino software (IDE) and implemented on the ATMega 2560 Microcontroller of the Arduino board. An ultrasonic sensor detects an obstacle and sends the data collected to the controller which directs the motor driver to stop or move the robot while following a visible predefined path (blackline) embedded in the ground and detected with the help of an IR sensor placed beneath the robot. Experimental results with varied obstacle positions show a decent performance scoring 96.4% accuracy at a 50cm distance to the obstacle.